Norm prevalence and interdependence: Evidence from a large-scale historical survey of German speaking villages - Radost Holler; Paul Schäfer (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We use large-scale survey data of German speaking villages from the 1930's to investigate drivers of cooperation, gender, and religious norms. Through geographic cluster analysis, we show that inter-regional variation explains only little heterogeneity in norms. Villages in the same physical and institutional environment still maintain different norms. We argue that local differences in the structure of social relationships can explain intra-regional heterogeneity in norms. We focus on a community's ability to transmit and enforce norms to derive theoretical links between correlates of community social relationships and the number of norms it maintains (norm prevalence). Empirically we find that: (1) norm prevalence is positively related to three correlates of community social relationships: religiously homogeneous villages, villages that border on other villages with a different majority religion, and villages with more within-village social gatherings; (2) villages with stronger community-level social relationships are also less likely to segment their reference group for the cooperation norm to smaller social units; (3) cooperation norms make other norms more likely.
Keywords: D03; J16; N94; Z10; Z12; 330; social norms; gender; religion; cooperation; culture; geography; communities